CAN ONE SPEAK OF TELEOLOGY IN PLATO? - Brisson, Luc (2021)
I would like to investigate here on an interpretive trend, one that invokes “teleology,” a compound term whose first element derives from the Greek telos, “end,” and the second from logos, “explanation”; the term ultimately refers to the final cause in Aristotle. The term “teleology” has become a relentless formula among those who now focus on Plato, Aristotle, and even the Stoics. In Plato, three places are particularly targeted: the autobiography of Socrates in the Phaedo (96e-99d), the Timaeus, and book X of the Laws. In this work in progress, I will limit myself to the Timaeus. I have worked hard on the Timaeus and, from the beginning, I wanted to read this text in and for itself, removing the thick layer of interpretations that, since the time of Aristotle, has covered this very original and enigmatic text.